Non-invasive Intraocular pressure monitoring with contact lens. Issue 9 (2nd July 2019) - Campigotto, Angelica; Leahy, Stephane; Zhao, Guowei; Campbell, Robert J; Lai, Yongjun
Abstract : Background: Glaucoma is the second leading cause of blindness in the world and the first leading cause of irreversible vision loss. Currently, the primary methodology of testing for the intraocular pressure (IOP) is during clinical office hours, which only provide a limited amount of information on the trends and fluctuations of the IOP. Therefore, a continuous monitoring system is required to properly determine the peaks of pressure and to negate any false results obtained by sparse, clinic hour testing. The objective of this study is to determine the ability of a newly designed contact lens with an embedded microchannel, to accurately measure the fluctuations in the IOP. Methods: Experimentation was completed on fresh enucleated porcine eyes. The contact lens was placed on the porcine eye and utilising a camera the fluid movement, within the microchannel in the contact lens, was recorded. A micro-pressure catheter, threaded into the centre of the vitreous chamber, recorded the true IOP and was compared with the displacement of the indicator fluid within the microchannel. Results: The contact lenses showed a consistent linear responsiveness to changes in IOP and robust to the effects of anatomical differences among eyes. The indicator fluid had an average fluid movement of 28 um/mm Hg between all the trials. Additionally, the devices showed the ability to measure both increases and decreases in IOP during cyclical fluctuations. Conclusion: The described inexpensive and non-invasive sensor is able to reliably monitor the IOP changes based on porcine eye model.